Feminist Existentialism in Donna Woolfolk Cross’s Pope Joan - Evelin Giovani; Arin Mantara Anggawirya; Nurul Istiqomah; Rosalia Floriani; Yuni Ratna Purwaningsih (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the representation of women in Donna Woolfolk Cross’s Pope Joan through the lens of Simone de Beauvoir’s existentialist feminism. The novel portrays a range of female experiences within a rigidly patriarchal religious and social system, making it a relevant and urgent site for analyzing how women navigate subordination, exercise agency, and construct resistance. This study aims to identify forms of women’s subordination, freedom, and resistance in the novel, and to classify the female characters according to Beauvoir’s typology: the Hetaira, the Narcissistic Woman, and the Mystical Woman. This descriptive qualitative study utilizes the text of Pope Joan as its primary data source, supplemented by secondary sources related to existentialist feminist theory. Data were collected through library research by reading, selecting, and classifying relevant excerpts. The analysis employed content analysis to identify scenes illustrating gendered power relations and women’s existential positioning, interpret them through Beauvoir’s concepts of immanence, transcendence, and otherness, and draw conclusions regarding the characters’ strategies of resistance. The findings show that Joan embodies the Hetaira who rejects immanence and pursues transcendence through education and critical reasoning. Gudrun and Richild represent the Narcissistic Woman, displaying limited and illusory autonomy shaped by patriarchal boundaries. Meanwhile, Gisla and Arn’s Mother exemplifies the Mystical Woman, fully internalizing patriarchal norms and accepting their subordinated role. These classifications reveal diverse existential responses toward patriarchy, and the novel also highlights that women’s agency emerges when they challenge imposed boundaries, affirming the relevance of Beauvoir’s existentialist feminism in literary analysis.